2009
DOI: 10.1109/jdt.2009.2013485
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor Polymer Disperse Microencapsulated Liquid Crystal Displays

Abstract: This work develops a new technology to fabricate polymer-dispersed microencapsulated liquid crystal (PDMLC) devices using screen-printing, which is a low temperature procedure (about 90 degrees C) for application on a soft plastic substrate. This research demonstrates numerically and in Mandarin, a 4.5-in multicolor PDMLC (MPDMLC) device with high color contrast, low electric consumption and flexible bending mechanical property. The current work coats three different color pastes (red, blue and black) on a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Microcapsules (4-10 mm) (Fig. 2) (Chen et al 2009) filled with an LC and a dichroic dye have been used to produce a paste applied as a varnish on a prepatterned indium tin oxide (ITO) coated polyethylene terephthalate (PET) substrate.…”
Section: Pdlc Preparation Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Microcapsules (4-10 mm) (Fig. 2) (Chen et al 2009) filled with an LC and a dichroic dye have been used to produce a paste applied as a varnish on a prepatterned indium tin oxide (ITO) coated polyethylene terephthalate (PET) substrate.…”
Section: Pdlc Preparation Techniquesmentioning
confidence: 99%
“…An example of a display obtained using PDLC-LV is shown in Fig. 9 (Huitema et al 2001), and others can be found in literature (Chen et al 2009) or on the Web (www. santechdisplay.com/en/product/show.asp?id = 17).…”
Section: Applicationsmentioning
confidence: 99%
“…It is also difficult to apply on the flexible wearable display field due to its membrane structure. To overcome these drawbacks, use of an independent microcapsule material with a DDLC core has been proposed as one of the most effective methods. ,, A DDLC-encapsulated polymer shell would not only form a three-dimensional independent structure but also protect the DDLC from the external environment and thus expands its application domain and prolongs the service life. Thus far, the microencapsulation technology has shown immense progress by employing various methods, such as microfluidic droplet generation, membrane emulsification, and layer-by-layer self-assembly methods. However, although these intelligent materials enhance the environmental stability and increase the application efficiency to some extent, they have a limited solar radiation modulation range that is restricted in the visible-light region and lead to a high level of transmittance in the high-frequency electromagnetic wave and near-infrared radiation (NIR) region.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study concerning fabricating CNLC microcapsules with a shell–core structure is mainly conducted by solute codiffusion method, emulsification polymerization, or phase separation method; however, there are several disadvantages when applying the above methods: first, the encapsulation efficiency of CNLCs in bulk polymer is not large enough and is difficult to be improved due to the random phase separation of a polymer matrix from continuous liquid phase into separated solid shell; second, the heterogeneous mixture consisting of CNLCs and polymerizable precursors hardly can be evolved into shell–core structured microcapsules with uniform size in the process of phase separation or emulsification polymerization; last, the direct contact between CNLCs and polymerizable precursors leads to the physical extrusion and chemical adhesion of neighboring microcapsule shells, making the shell morphology exhibit an irregular sphere or ellipsoid.…”
Section: Introductionmentioning
confidence: 99%